Creating and capturing value in KAM relationships - Ryals, Lynette; Holt, Sue (Taylor & Francis, 2007)
Questions have recently been raised about whether key account management (KAM) pays off for suppliers. Previous research has been equivocal on this issue. Yet suppliers are increasingly adopting (or being forced by their customers to adopt) KAM, which could be problematic if the supplier is unable to capture value from the relationship. This research examines how suppliers capture value from KAM. First, supplier-influenceable aspects of the value of the customer are explored through an elucidation of the drivers of customer revenues and costs. Then, value capture in KAM relationships is examined through the lens of five research propositions. The first result of the research contributes to theory with a detailed model of the drivers of customer lifetime value. The second result contributes to KAM practice through a confirmation of the five propositions and an exploration of how ten good practice companies capture value from their KAM relationships.
Keywords: Customer profitability; customer lifetime value; key account management; value capture